Development of Animal Models for Adeno-Associated Virus Site-Specific Integration - Rizzuto, Gabriella (American Society for Microbiology, 1999)
The adeno-associated virus (AAV) is unique in its ability to target viral DNA integration to a defined region of human chromosome 19 (AAVS1). Since AAVS1 sequences are not conserved in a rodent’s genome, no animal model is currently available to study AAV-mediated site-specific integration. We describe here the generation of transgenic rats and mice that carry the AAVS1 3.5-kb DNA fragment. To test the response of the transgenic animals to Rep-mediated targeting, primary cultures of mouse fibroblasts, rat hepatocytes, and fibroblasts were infected with wild-type wt AAV. PCR amplification of the inverted terminal repeat (ITR)-AAVS1 junction revealed that the AAV genome integrated into the AAVS1 site in fibroblasts and hepatocytes. Integration in rat fibroblasts was also observed upon transfection of a plasmid containing the rep gene under the control of the p5 and p19 promoters and a dicistronic cassette carrying the green fluorescent protein (GFP) and neomycin (neo) resistance gene between the ITRs of AAV. The localization of the GFP-Neo sequence in the AAVS1 region was determined by Southern blot and FISH analysis. Lastly, AAV genomic DNA integration into the AAVS1 site in vivo was assessed by virus injection into the quadriceps muscle of transgenic rats and mice. Rep-mediated targeting to the AAVS1 site was detected in several injected animals. These results indicate that the transgenic lines are proficient for Rep-mediated targeting. These animals should allow further characterization of the molecular aspects of site-specific integration and testing of the efficacy of targeted integration of AAV recombinant vectors designed for human gene therapy.